Virtual Consultations—“Should We Be Using Them?”: A Two-Cycle Clinical Audit - Lee, Yung Wei Jarred; Patel, Anika; Acharya, Sandeep; Seshu, Madhavi (European Journal of General Dentistry, 2022)
Objective In response to the coronavirus disease 2019 pandemic, the use of virtual appointments increased substantially. An audit was designed to evaluate the efficacy of virtual appointments at Alder Hey Children's Hospital. Patients and clinicians satisfaction of virtual appointments were also recorded.Materials and Methods Patients having virtual appointments were identified, and data were recorded, including demographics and outcome of the appointment. A pilot study was conducted to identify any necessary modifications to the data collection process. Data were collected over two cycles, and the results were analyzed.Results The first cycle was performed retrospectively and there were 158 patients identified who had a virtual appointment. An outcome could be drawn from the virtual appointment in over 70% of cases. Recommendations following the first cycle were implemented. A second cycle was then completed prospectively. A total of 145 patients were identified. An outcome could be drawn in 51% of cases. Patient and clinician feedback on virtual appointments was generally positive.Conclusion This study demonstrated that a successful outcome could be drawn in the majority of virtual appointments, and clinicians and patients had positive experiences regarding virtual clinics. This highlights the usefulness of this service, which is particularly relevant due to the increased reliance on virtual clinics during the pandemic.
Keywords: audit; virtual; coronavirus